Pengaruh Penggunaan Media Audio Visual Terhadap Minat Belajar Siswa di MIM 1 PK Sukoharjo - Hidayah, Nur; Hidayatul Amin, Lailla; Dwi Kasanah, Wati (Indonesian Journal of Islamic Elementary Education, 2022)
Education is one of the driving factors for determining superior human resources for the progress of the nation. The existence of the media will help achieve goals more effectively and efficiently. Thematic learning is an integrated learning that uses a theme as the main focus and provides a meaningful experience for students as a whole. The low interest in students' learning as indicated by the value of students who have not achieved minimum mastery is the background of this research, so thatthe use of audio-visual media is examined for its influence on integrative thematic learning.This study uses a quantitative research approach with a descriptive correlation model and was carried out in February 2020 with a population of 210 students and a sample of 70students. The data collection techniques used observation, interviews, documentation and questionnaires. The results of this study concluded that: 1) the use of audio-visual media in integrative thematic learning was in the good category, with a percentage of 52.86% or 37 students, 2) students' interest in learning in integrative thematic learning was in the good category with a percentage of 48, 57% or 34 students, and 3) The use of audio-visual media has a positive effect on learning interest in integrative thematic learning with r0 = 0.624 greater than r1 at a significant level of 5% (r1 = 6.235) and 1% (r1 = 0.306). Madrasas are expected to learn more often using audio-visual media, especially material that may not be accessible to students' minds. Audio visual media learning can be applied at all grade levels.